FEATURES OF CONDUCTING INVESTIGATIVE ACTIONS UNDER MARTIAL STATE IN UKRAINE - Litvinova, Iryna; Dmytrenko, Maryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is a comprehensive analysis of the features and problems of legal regulation and tactics of conducting investigative (search) actions under martial law in Ukraine, as well as the development of proposals for improving criminal procedural legislation and investigative practice taking into account modern challenges and international experience. Research methods: formal-legal, comparative-legal, systemic-structural, as well as methods of analysis, synthesis and generalization. The results of the study demonstrate that the legal regime of martial law has led to a significant transformation of the criminal procedural order of conducting investigative actions, which was expressed in the introduction of legislative amendments and the limitation of procedural guarantees in order to adapt to security challenges. It has been established that investigative practice faces a number of systemic problems, in particular, delays in registering proceedings in the ERDR, risks to the safety of participants, which requires the development of new tactical approaches, and difficulties in properly recording evidence. It has been proven that the use of remote formats for interrogation and presentation for identification is debatable and may violate procedural guarantees and affect the reliability of evidence. The growing role of covert investigative actions in countering crimes against national security and the importance of borrowing international experience, in particular from Israel, in the field of coordination of investigative bodies and the use of technology are substantiated. Discussion: adapting the criminal procedure order to the conditions of martial law is a forced step that creates significant tension between the needs of effective investigation and compliance with fundamental procedural guarantees. Practical challenges, such as the safety of investigators and proper fixation of evidence in a combat zone, require not only legislative changes, but also the development of new tactical techniques and enhanced interagency coordination, as the experience of Israel shows. Although digitalization and remote formats offer certain solutions, their application must be balanced in order to avoid leveling the key principles of criminal proceedings. Further improvement requires the creation of flexible but clearly regulated mechanisms that will allow law enforcement agencies to respond promptly to threats without violating fundamental human rights.